Incidence and predictors of hemodynamic compromise due to high-grade AV block after TAVI - Weferling, Maren; Lan Cheong Wah, Stefan; Fischer-Rasokat, Ulrich; Hain, Andreas; Renker, Matthias; Charitos, Efstratios I.; Liebetrau, Christoph; Treiber, Julia; Choi, Yeong-Hoon; Hamm, Christian W.; Kim, Won-Keun (Frontiers in Cardiovascular Medicine, 2023)
Background: High-grade AV block (HAVB) is the most frequent adverse event after transcatheter aortic valve implantation (TAVI). In rare cases, HAVB is associated with hemodynamic compromise (HC) followed by syncope or application of cardiopulmonary resuscitation (CPR), but data on this severe complication are scarce. The aim of the present study was to investigate the incidence and predictors of HC due to HAVB in patients undergoing TAVI. Methods: In this retrospective analysis of 4602 TAVI cases between 2010 and 2022, 466 developed HAVB. Baseline characteristics and procedural and postprocedural findings were compared for patients with HC versus those without. Univariate and multivariable regression analyses were used to investigate independent predictors of HC. Results: Forty-nine of 466 patients (10.5%) had HC due to HAVB after TAVI. Patients with HC had a longer hospital stay (10 [8-13] vs. 13 [9-18] days; p<0.001), more frequent peripheral artery disease (PAD) (28.6% vs. 15.1%; p=0.016), and lower hemoglobin levels (11.8 [±1.6] vs. 12.5 [±1.8] g/dl; p=0.006). In the HC group, HAVB onset post-TAVI was delayed compared with the non-HC group (2 [1-4] vs. 1 [0-3] days; p<0.001). Before HAVB onset, patients in the HC group more frequently developed post-TAVI delirium (18 [4.6%] vs. 11 [25.0%]; p<0.001). In univariate regression analysis, PAD, hemoglobin, procedural time, contrast agent volume, and post-TAVI delirium were significant predictors of HC. After adjustment, only post-TAVI delirium and contrast agent volume remained independent predictors (OR 3.22 [95% CI 1.05-9.89]; p=0.042 and OR 1.01 [95% CI 1.0-1.01]; p=0.04, respectively). Conclusion: HC due to HAVB after TAVI occurred in over 10% of cases. Development of post-TAVI delirium and contrast agent volume are independent predictors of this severe complication.